Atezolizumab, vemurafenib, and cobimetinib as first-line treatment for unresectable advanced BRAFV600 mutation-positive melanoma (IMspire150): primary analysis of the randomised, double-blind, placebo-controlled, phase 3 trial. Issue 10240 (13th June 2020) - Gutzmer, Ralf; Stroyakovskiy, Daniil; Gogas, Helen; Robert, Caroline; Lewis, Karl; Protsenko, Svetlana; Pereira, Rodrigo P; Eigentler, Thomas; Rutkowski, Piotr; Demidov, Lev; Manikhas, Georgy Moiseevich; Yan, Yibing; et al.
Summary: Background: IMspire150 aimed to evaluate first-line combination treatment with BRAF plus MEK inhibitors and immune checkpoint therapy in BRAF V600 mutation-positive advanced or metastatic melanoma. Methods: IMspire150 was a randomised, double-blind, placebo-controlled phase 3 study done at 112 institutes in 20 countries. Patients with unresectable stage IIIc–IV, BRAF V600 mutation-positive melanoma were randomly assigned 1:1 to 28-day cycles of atezolizumab, vemurafenib, and cobimetinib (atezolizumab group) or atezolizumab placebo, vemurafenib, and cobimetinib (control group). In cycle 1, all patients received vemurafenib and cobimetinib only; atezolizumab placebo was added from cycle 2 onward. Randomisation was stratified by lactate dehydrogenase concentration and geographical region. Blinding for atezolizumab was achieved by means of an identical intravenous placebo, and blinding for vemurafenib was achieved by means of a placebo tablet. The primary outcome was investigator-assessed progression-free survival. This trial (ClinicalTrials.gov, NCT02908672 ) is ongoing but no longer recruiting patients. Findings: Between Jan 13, 2017, and April 26, 2018, 777 patients were screened and 514 were enrolled and randomly assigned to the atezolizumab group (n=256) or control group (n=258). At a median follow-up of 18·9 months (IQR 10·4–23·8), progression-free survival as assessed by the study investigator was significantly prolonged with atezolizumab versus control (15·1 vs 10·6 months; hazard ratio [HR] 0·78; 95% CI 0·63–0·97; p=0·025). Common treatment-related adverse events (>30%) in the atezolizumab and control groups were blood creatinine phosphokinase increased (51·3% vs 44·8%), diarrhoea (42·2% vs 46·6%), rash (40·9%, both groups), arthralgia (39·1% vs 28·1%), pyrexia (38·7% vs 26·0%), alanine aminotransferase increased (33·9% vs 22·8%), and lipase increased (32·2% vs 27·4%); 13% of patients in the atezolizumab group and 16% in the control group stopped all treatment because of adverse events. Interpretation: The addition of atezolizumab to targeted therapy with vemurafenib and cobimetinib was safe and tolerable and significantly increased progression-free survival in patients with BRAF V600 mutation-positive advanced melanoma. Funding: F Hoffmann–La Roche and Genentech.